Effect of amino acid supplementation on performance of Soviet Chinchilla weaners fed mustard-cake-based diet - BHATT, R S; BHASIN, V; BHATIA, D R (The Indian Journal of Animal Sciences, 2013)
Kits (28) of Soviet Chinchilla breed, weaned at 42 days age, individually received ad lib. for 42 days a solvent extractedmustard-cake-based (24%) complete mash diet with or without 0.1% lusine or methionine. An increas of 28.33% in liveweight gain and 20.30% in feed conversion ratio was observed in methoionine supplemented group. The intake of DCP.TDN, N-utilization and EE digestibility improved with tile supplementation of methionine. It could be concluded thatmethionine supplementation resulted in higher gain, better feed conversion and dressing per cent in animals receiving the testdiet.